Large improvement of thermal transport and mechanical performance of polyvinyl alcohol composites based on interface enhanced by SiO2 nanoparticle-modified-hexagonal boron nitride. (5th January 2019) - Zhang, Jun; Li, Chaowei; Yu, Cuiping; Wang, Xiaona; Li, Qiulong; Lu, Huifen; Zhang, Qichong; Zhao, Jingxin; Songfeng, E.; Hu, Ming; Yao, Yagang
Abstract: The interface plays a key role in determining the properties of polymer composites. However, chemical inertness of hexagonal boron nitride (h-BN) makes its surface modification troublesome. In this study, we, for the first time, used SiO2 as the modified molecular and investigated the effects of exfoliated h-BN and SiO2 nanoparticles-modified-exfoliated h-BN (SiO2 @exfoliated h-BN) on the storage modulus, the glass transition temperature, the filler dispersion and the thermal conductivity of polyvinyl alcohol (PVA) composites prepared by a solution mixture method. The results showed that the SiO2 modification enhanced the interface interaction and improved the performance of the PVA composites. Based on the enhanced interface interaction by SiO2 modification and the aligned fillers in PVA by vacuum filtration, the high thermal conductivity of 13.88 W/m·K was realized at 15.2 wt% SiO2 @exfoliated h-BN loading. Meanwhile, the tensile strength was also largely improved to 156 MPa, compared with 47 MPa of pure PVA. This study broadens the surface modification method of h-BN and provides a valuable reference for fabrication of high-performance thermal interface materials.